Intestinal pediculated graft applicated to a experimental gastric perforation - Alberti, Carlos Daniel; Abella, Manuel; Verdinelli, Humberto; Mombello, Raúl; Fabrizio, Claudio; Barrionuevo, Adolfo; Travizano, Enrique; Carbajo, Jorge; Delgado, Eduardo; Domínguez, Juan Carlos (Cirugía del Uruguay, 1983)
On the basis that intestinal s ubmucosal corion in dogs, may resist chloridropeptical action, in 40 dogs an intestinal graft without mucosa was applicated to a gastric perforation, observing that on 60 days, in 14 of the 20 sacrified dogs, gastric mucosa has reepitalized the graft.